Acquisition and Data Logging Inertial Navigation System (INS) on Combat Submarine Using Arduino-SD Card - Varisa Rahmawati; Achmad Affandi; Imam Arifin; Muhammad Asrofi (Institut Teknologi Sepuluh Nopember, 2019)
In a combat submarine operating system, navigation device acts as a location information provider on inside or at sea level. Such information is position data provided by GPS (Global Positioning System) and data transmitted by IMU (Inertial Measurement Unit) sensor. Combining these two device is called INS (Inertial Navigation System). This inertial sensor interacts using serial communication data, however records are needed to collect, store and store incoming data in order to be processed easily. Data logging process is feasible as a recorder and data storage using SD Card. Enhancements, such as SD cards are needed because in general system is equipped with a small memory capacity. Arduino is a microcontroller that can assist in process because data obtained from sensor is processed using serial communication lines (RX and TX). Results obtained from calculation and logging data are calculation Roll, Pitch, Heading, Latitude, Longitude, Microseconds, Gyroscope on X axis, Y, Z, Accelerometer on X axis, Y, Z, Magnetometer on X, Y, Z, Velocity North, East, Down. This proves that system acceleration and data logging using Arduino and SD Card can assist in obtaining information and KTBA situations